A review on anti-nutritional factors: unraveling the natural gateways to human health - Salim, Rehana; Nehvi, Iqra Bashir; Mir, Rakeeb Ahmad; Tyagi, Anshika; Ali, Sajad; Bhat, Owais M. (Frontiers in Nutrition, 2023)
Humans are constantly facing multiple health challenges from both communicable and non communicable diseases that significantly affect their health. Additionally, drug resistance or their failure has made the situation even worse and possess serious challenges for researches to develop new drugs. Hence, to address these problems there is urgent need to discover and develop timely and long term based therapeutic treatments from different sources. One such approach is harnessing the potential of plant secondary metabolites. Nevertheless, plants have been utilized for therapeutic purposes in addition to being used for nutritional benefits. From last two decades, plant based drug developments has been one of the effective means to treat human diseases owing to their multiple functions. More recently, Anti-nutritional factors (ANFs) have emerged as one of the important targets for novel plant-based drug development owing to their multifaceted and potential pharmacological properties. However, their antinutritional properties have been the major setback for their limited success in pharmacological sectors. In this review, we provide an overview on ANFs and their beneficial roles in preventing human diseases with multiple case studies. We also highlight the recent developments and applications of ANFs in the food industry, agriculture, and pharmaceutics with future perspectives. Furthermore, we evaluated meta-analyses on ANFs from the last 30 years in relation to their function in human health benefits. This review is an endeavor to reevaluate the merit of these natural compounds to probe their potentials for the benefit of humans and animals.